The Politics of Limitation of Claims in Poland: Post-Communist Ideology, Neoliberalism and the Plight of Uninformed Debtors - Kuźmicka-Sulikowska, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The text will present arguments raised by the supporters of two different positions regarding the manner of taking into account the expiry of the limitation period, namely those that are supposed to speak in favor of taking this circumstance by the courts ex officio, and those which prevail to take it into account only in the event of raising the plea of limitation by the one against whom the claim is due. Against this background, a polemical analysis will be made with these arguments, including inquiries about interests of which entities or social groups are implemented and protected for each of these solutions. It will be shown that some of the arguments put forward actually emphasize that the institution of limitation is to serve not so much as a party involved in a given claim (creditors or debtors), but rather institutions of the judiciary. It will also be shown that the solution currently in force in Polish civil law, within which the taking into account of the fact that a given claim is time-barred is possible only if the one against whom the claim is entitled raises the relevant claim of limitation, in fact prefers only the more affluent and better educated social strata, deepening the social exclusion of those who, due to, for example, worse property status, do not have the necessary knowledge, nor can afford to take advantage of legal aid. The latter, in effect, often do not plead the expiration of limitation period, because they do not know that they are entitled to it (in general, or are unable to assess when the claim became due, at which point the limitation period began or has ended). Polish civil law is a good example here for considering, firstly, that in the 20th century the regulations concerning the limitation of claims were changed several times, and each time a discussion on how to consider the expiry of the limitation period came to life (which provides rich argumentation with which one can confront) and also because historical and political entanglements play a significant role here. Namely, the text will show that the main resistance against taking into account the expiration of limitation period ex officio (which is a solution that protects the poorer people who can not afford legal assistance) is due to the fact that this solution, which was in force in the original version of the current Polish Civil Code, was modeled on the solutions of Soviet law. This means that after the political change in Poland in 1989, it was automatically attempted to eliminate it, and replace it with a solution used in European countries, where only if the one against whom the claim is entitled raises the relevant claim of limitation, even without any reflection on the substantive legitimacy of such a change and without analyzing the practical social effects of a solution, within which the expiry of the limitation period only is taking into account on when relevant plea is raised, not ex officio. Immersion of considerations in the realities of Polish law will also allow to show interests that have recently clashed on the occasion of the regulation of electronic writ-of-payment proceedings. In this example, it will be shown that despite the legislator making certain facade measures to protect the interests of people with less legal awareness and poorer, who can not afford to get help from a lawyer, in fact, many gates have been left, which question the reality of striving for such protection, because they allow to sue for the claim after the expiration of the limitation period in this proceeding. In this context, the latest change in Polish civil law in this area was also discussed, that is, the Act of April 13, 2018. On the basis of this Act, there has been a return to taking into account the expiration of the limitation period ex officio, but only if the entrepreneur sue the consumer. In the remaining scope, a solution was left within which the expiry of the limitation period is taking into account only when relevant plea is raised.